A multiple‐gene phylogeny reveals polyphyly among eastern North American Aphaenogaster species (Hymenoptera: Formicidae). (27th January 2016) - DeMarco, Bernice B.; Cognato, Anthony I.
Abstract : Twenty‐three Aphaenogaster species (Hymenoptera: Formicidae) occur in North America. While morphology and ecology define most species, the species limits of a group in the Eastern United States are unclear. In particular, the morphological and behavioural characters of A. carolinensis, A. picea and A. rudis overlap. These observations suggest that these three species are not monophyletic. We therefore tested the monophyly of Aphaenogaster in the context of molecular phylogenetic analyses. We used DNA data from five genes: CO1, CAD, EF1αF2, long‐wavelength rhodopsin and wingless, to reconstruct phylogenies for 44 Aphaenogaster and outgroup species. In the resulting trees, reconstructed using parsimony and Bayesian inference, species boundaries associated with well‐supported monophyletic clades of individuals in most of the 23 North American Aphaenogaster collected from multiple locations. However, some clades were unresolved, and both A. picea and A. rudis were not monophyletic. Although this may indicate that clades of multiple species represent fewer but morphologically varied species, given the short branch lengths, the lack of resolution may reflect the fact that these ants have recently radiated, and a lack of gene lineage sorting explains the non‐monophyly of species. Additional biological information concerning pre‐ and postmating barriers is needed before a complete revision of species boundaries for Aphaenogaster .